Community Participation Dynamics in the Land Registration Process in the Digital Era and the Challenges Faced - Robbani, Muhammad Rizqi; Meidianto, Muhammad Rizki; Nadhif, Faza Fatkhun; Niravita, Aprila; Fikri, Muhammad Adymas Haikal (PT Maju Malaqbi Makkarana, 2024)
This article aims to examine the dynamics of community participation in the land registration process in the digital era, as well as the challenges faced in optimizing citizen involvement. In the midst of developments in digital technology, land registration has great potential to become more transparent and efficient. However, although information technology can facilitate access to information and speed up the registration process, there are a number of challenges that need to be overcome. These challenges include the digital divide, low technological literacy among the community, and a lack of understanding of land rights. This research uses qualitative methods to find out people's experiences in participating in the land registration process and find ways to make people more active. It is hoped that the results of this research can provide advice to the government and related parties so that people can participate more easily and everyone feels involved.